Pengaruh media Visual terhadap peningkatan kemampuan berbicara bahasa Arab siswa - Muhammad Sholeh; Laili Mas Ulliyah Hasan (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2024)
This study aims to evaluate the impact of visual media on the enhancement of students' Arabic speaking skills. In the digital age, visual media such as videos, images, and graphics play a significant role in language learning processes. The research employs an experimental method involving two groups of students: one group uses visual media in their learning process, while the other group follows conventional teaching methods. The results indicate that students exposed to visual media show a significant improvement in their Arabic speaking abilities compared to the control group. These findings suggest that visual media can be an effective tool for enhancing Arabic speaking skills by providing visual context that supports better understanding and use of the language.